2022
DOI: 10.1186/s12917-021-03104-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Mycoplasma Synoviae strains isolated in China from 2016 to 2019

Abstract: Background In the past decade, Mycoplasma synoviae (M. synoviae) infection has become widely prevalent in China, has caused serious economic losses and has become one of the most important diseases in the chicken industry. Medication is a general approach for the control of M. synoviae infection, but antibiotics are sometimes ineffective in clinical practice. To investigate the sensitivity of M. synoviae to antimicrobials commonly used in the treatment of M. synoviae infection, the antibiotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Enrofloxacin had high MIC values for all M. synoviae isolates (Catania et al 2019). Zhang found that enrofloxacin generally had high MIC values for some of the M. synoviae isolates (Zhang et al 2022). A comparison of the parC quinolone Using an in vivo model of M. synoviae infection in chickens, we found that all treatment groups achieved good therapeutic effects 14 days after drug withdrawal, and doxycycline had one of the best treatment effects, along with tylvalosin.…”
Section: Discussionmentioning
confidence: 77%
“…Enrofloxacin had high MIC values for all M. synoviae isolates (Catania et al 2019). Zhang found that enrofloxacin generally had high MIC values for some of the M. synoviae isolates (Zhang et al 2022). A comparison of the parC quinolone Using an in vivo model of M. synoviae infection in chickens, we found that all treatment groups achieved good therapeutic effects 14 days after drug withdrawal, and doxycycline had one of the best treatment effects, along with tylvalosin.…”
Section: Discussionmentioning
confidence: 77%
“…MS infection is very common in aviculture around every region of the world, with exceptionally high rates in China, Egypt, and Ethiopia, giving rise to great economic losses to countries [5][6][7]. In recent years, the clinical and economic relevance of MS seems to be increasing, and its harm may exceed Mycoplasma gallisepticum [8].…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence from in vitro and animal studies proves that EOs have multiple biological activities, such as anticancer [4,5], antiviral [6][7][8][9], antibacterial [10][11][12][13], antifungal [14,15], antibiofilm [16][17][18], anti-inflammatory [19][20][21], and antioxidant [19,[22][23][24][25] effects, which constitute the starting point for the in vivo assessment of those properties in various therapeutic and cosmetic fields [26][27][28][29][30][31][32][33]. Nevertheless, since great consideration has been given to the effective use of EOs in clinical procedures, further systematic animal studies and clinical investigations are needed.…”
Section: Introductionmentioning
confidence: 99%